2000
DOI: 10.1095/biolreprod63.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Estrogen Receptor Coactivators in the Rat Uterus1

Abstract: Nuclear receptor coactivators associate in a ligand-dependent manner with estrogen receptors (ER) and other nuclear receptors, and they enhance ligand-dependent transcriptional activation. This study examined basal coactivator expression in rat uterus to investigate if expression of these genes is regulated by estradiol-17 beta or tamoxifen. Ovariectomized mature and immature rats were injected with estradiol-17 beta, tamoxifen, or vehicle (i.e., sesame oil) alone. Uteri were collected and analyzed for changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 38 publications
5
25
0
Order By: Relevance
“…This is in agreement with other studies in which estradiol treatment did not regulate the expression of TIF1a, AIB1, SMRT or SRC-1 in MCF-7 cells (52) or SRC-1, glucocorticocoid receptor-interacting protein-1, AIB1, receptor-interacting protein-140 or p300 in the rat uterus (63). Yet there is evidence that some cofactors are regulated by estradiol.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with other studies in which estradiol treatment did not regulate the expression of TIF1a, AIB1, SMRT or SRC-1 in MCF-7 cells (52) or SRC-1, glucocorticocoid receptor-interacting protein-1, AIB1, receptor-interacting protein-140 or p300 in the rat uterus (63). Yet there is evidence that some cofactors are regulated by estradiol.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, SRC-1 mRNA levels have been reported to be insensitive to E 2 in the uterus of the rat. SMRT mRNA expression is reported to be low and unchanged after secretagogue stimulation (Nephew et al 2000). In this study, we found low levels of SRC-1 mRNA in untreated cells; however, in the presence of forskolin or AII, SRC-1 mRNA levels were increased.…”
Section: Discussionsupporting
confidence: 48%
“…Although studies had reported SRC-2 expression in the human and rodent female reproductive tract (11,28,29,33,42,47), a more comprehensive immunohistochemical study was required to determine whether P-responsive cell lineages within reproductive tissues of the cycling mouse express SRC-2. Nuclear SRC-2 immunoreactivity was detected in the uterine epithelium (luminal and glandular compartments), as well as throughout the underlying stroma and myometrium ( Fig.…”
Section: Resultsmentioning
confidence: 99%